(3GdhTi GdeQbhe aj Md GdefXhes - (3fUQ Gddg Hf eMeO Hf eMeO Hf YHO GdcQje GdTjHGfqj, GdLRQj, CHh GdaJM, VjGA GdOjf, GdeYQha HGHf GdCKjQ GdcGJH,J (B637 (3g` s
(3ChdgG (B:s
(3CMeO Gddg Ydi aVjdI GdfWb hHjGfg CeG HYO aEf dcJGHI GdEfTGA dHkG hbTQkG hHWfkG hXgQkG GYde Cf GdcGJH jMJGL Edi GdJTHK Hcd af hGdfXQ ai cd Yde s
(3BNQgG (B:s
(3hai gPG GdOYGA eYfi ef GdCNHGQ GdfHhjI hgh Cfg cGf EPG MVQJ GdUdGI bGd GdfHi Udi Gddg Ydjg hSde dHdGd QVi Gddg Yfg CQMfG HgG jG HdGd Ci YLd HgG Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B98s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2012s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(898) s
Keywords: (3GdCOHs